The Role of Gender in the Audit Committee as a Moderator on the Determinants of Indications of Financial Statement Fraud in Banking: A Fraud Hexagon Perspective - Juliarta, I Wayan; Tungga Atmadja, Anantawikrama; Sri Werastuti, Desak Nyoman (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2024)
This research aims to empirically prove the factors that lead the board of directors to commit financial statement fraud. These factors are explained and interpreted based on the elements found in the fraud hexagon theory. The study also aims to empirically demonstrate that the gender of the audit committee within the company can weaken the actions of the board of directors that lead to fraudulent behavior in financial statements. The research sample was selected using purposive sampling techniques, resulting in 41 companies that met the criteria, with observations over a period of 5 years from 2019 to 2023. Data were collected by downloading annual reports and audited annual financial statements. The data analysis technique employed binary logistic regression, analyzed using Stata software. The results indicate that capability and opportunity have a positive effect on indications of financial statement fraud. Stimulus, collusion, rationalization, and ego do not have an effect on indications of financial statement fraud. The gender of the audit committee does not moderate the influence of stimulus, capability, collusion, opportunity, rationalization, and ego on indications of financial statement fraud.